Strengthening the Regulatory Aspects of Special Economic Zones in Indonesia as a Key Factor Driving Economic Growth in Indonesia - Setiadi, Elen; Herman, KMS (Devotion : Journal of Research and Community Service, 2025)
Special Economic Zones (SEZs) have a strategic role in driving national economic growth through increased investment, job creation, and strengthening industrial competitiveness. However, the implementation of SEZs in Indonesia still faces various regulatory obstacles that hinder the effectiveness and optimization of the potential of the area. This study aims to analyze the importance of strengthening regulatory aspects in SEZ management as the main factor in accelerating Indonesia's economic growth. Using a normative legal approach and policy analysis, this study finds that regulatory harmonization, ease of licensing, and legal certainty are crucial elements in creating a conducive business climate in SEZs. Integrated and adaptive regulatory reforms to global dynamics are needed to optimize the role of SEZs as the driving force of the national economy.